Ella Maher interviewed by Judy Wing in the NSW Bicentennial oral history collection - Maher, Ella, 1907-1994; Wing, Judy; N.S.W. Council on the Ageing; Oral History Association of Australia. N.S.W. Branch; NSW Bicentennial Oral History Project (1987)
Born at Inverell, NSW, Maher speaks of her parents background ; childhood memories of life in the country ; parents hotels in various parts of NSW ; attending convent boarding school in Tamworth from age 7, experiences there ; other students, lifestyle ; her education ; attending Sydney Teachers College ; lifestyle in Sydney ; living in a boarding house ; teaching in Sydney and living with maiden aunts as mother would not let her flat with girlfriends ; her teaching course, experiences teaching in the country ; teaching methods, schools, classes.
Recorded by the NSW Bicentennial Oral History Project, funded by a bicentennial grant to the NSW Council on the Ageing and the Oral History Association of Australia (NSW).
Also available online
Timed summary and transcript available.
Keywords: Maher, Ella, -- 1907-1994 -- Interviews; Older people -- New South Wales -- Biography; Women -- New South Wales -- Social conditions -- 1901-1945.; Women teachers -- New South Wales -- Biography; Teachers